Genomic characterisation of extensively drug-resistant Acinetobacter baumannii isolates from a tertiary hospital in Ghana - Isabella E. Ashley-Agbedor; Samiratu Mahazu; Fleischer C. N. Kotey; Jennifer Amedior; Bright Adu; Emmanuel Darko; Paul Kwao; Nicholas T. K. D. Dayie; Anthony S. Ablordey; Japheth A. Opintan (PLoS ONE, 2026)
Acinetobacter baumannii ( A. baumannii ) is an emerging “superbug” whose infections have become extremely difficult to treat due to its diverse antimicrobial resistance mechanisms and resistance to last-resort antibiotics including carbapenems. Despite this, data on genetic determinants and genomic context of carbapenemase genes in A. baumannii are scarce in Ghana. This study investigated the genetic determinants of carbapenem resistance in clinical isolates of A. baumannii ( Ab ) and explored the genetic contexts of carbapenemase-encoding genes in extensively drug-resistant A. baumannii (XDR- Ab ). We analysed 65 archived clinical A. baumannii isolates. Identification and antimicrobial susceptibility profiles of the isolates were determined using a MALDI-TOF-MS and the Microscan device, respectively. Carbapenem resistant A. baumannii (CR- Ab ) isolates were screened for carbapenemase-encoding genes ( bla NDM-1 , bla KPC , bla VIM , bla OXA-48 , bla OXA-23 , bla OXA-58 , and bla IMP ) using loop-mediated isothermal amplification (LAMP). Six XDR- Ab isolates were whole-genome sequenced (WGS) using Nanopore MinION. Carbapenem resistance was observed in 18/65 (27.7%) isolates. All CR isolates were resistant to penicillins, cephalosporins, fluroquinolones, aminoglycosides, sulfonamides and carbapenems (minimum inhibitory concentrations, MICs, > 2µg/ml - > 8µg/ml). The most predominant resistance gene, bla NDM-1 (33.3% ) , was found to co-exist with bla OXA-23 (27.8%) or bla OXA-58 (16.7%), while bla OXA-420 (12.5%) was the least prevalent gene detected. The sequence types identified among the isolates were ST2 (33.3%), ST164 (16.7%), ST214 (16.7%), ST52 (16.7%), and ST16 (16.7%) according to MLST-Pasteur scheme. The study highlights the carriage of multiple carbapenemase genes, other AMR-encoding genes and efflux pumps in XDR clinical A. baumannii isolates. To the best of our knowledge, the study reports for the first time, the detection of ST2 OXA-23, NDM-1 and ST164 OXA-58, NDM-1-producing A. baumannii strains at the Korle Bu Teaching Hospital. These strains belong to high-risk clones and continuous surveillance through molecular epidemiological studies and public health interventions are urgently needed to control their spread in Ghana.